THE ROLE OF LIFE SKILLS IN ENHANCING ADOLESCENTS’ QUALITY OF LIFE THROUGH SPORT ACTIVITIES: A SYSTEMATIC LITERATURE REVIEW - Elhaqe, Qintarazany M; Hidayat, Yusuf; Kusnaedi, Kusnaedi (Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
Adolescents worldwide will face life challenges that are uncertain and complex in this modern era. Life skill and sport participation are two crucial factors that can potentially assist adolescents in coping with life challenges and enhancing their quality of life. This study aims to investigate the role of life skills in enhancing adolescents’ quality of life through physical activity or sports. The research method is employing a systematic literature review that combined terms relating to life skill AND sport OR physical activity OR physical activities that was published in 2013 - 2023. Ten out of 346 scientific articles met the inclusion criteria. The research findings revealed that life skills intervention effectively demonstrated in addressing various life domains to improve adolescents’ quality of life. Sport activities serve as an effective means of teamwork, communication, emotional management, decision-making, and more. In conclusion, these findings provide compelling evidence for parents, policymakers, educators, and others to promote active participation of adolescents in sports activities, which can improve life skills and positively impact their long-term quality of life.